The Impact of Couple Stress on Thermosolutal Instability of Visco-Elastic Nanofluids in Porous Medium (Journal of Scientific Research, 2025)
This work aims to investigate the impact of couple stress on the thermosolutal convection of viscoelastic nanofluid saturated in the porous medium. The rheological behavior of a viscoelastic nanofluid is characterized by the Rivlin-Erickson model. We study the linear stability analysis using the normal mode analysis method and examined analytically and graphically using MATLAB the impact of non-dimensional factors such as the couple stress, the concentration Rayleigh number, the solutal Rayleigh number, the thermos-nanofluid Lewis number, the thermosolutal Lewis number, Dufour and the Soret parameters and found that the couple stress, nanofluid Lewis number and modified diffusivity ratio enhance the instability of thermosolutal convection.